2009
DOI: 10.1309/ajcpkwuqsipvg90h
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis in Esophageal Adenocarcinomas--Lymphatic Vessel Density as Prognostic Marker in Esophageal Adenocarcinoma

Abstract: We studied tumor lymphatic vascular density (LVD) as a predictive marker for the risk of lymph node (LN) metastasis and its relationship to other prognostic parameters and survival in 75 patients with esophageal adenocarcinoma. Samples were immunostained for D2-40, CD31, and vascular endothelial growth factor (VEGF). Microvessels were counted in densely vascular/lymphatic foci (hot spots) at x400 field (0.17 mm2). Intensity of staining for VEGF was scored on a 2-tiered scale. CD31 microvessel counts showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…We THORACIC SURGERY also found that the presence of both itLVI and ptLVI significantly correlated with tumor size, tumor depth, TNM stage, and residual tumor. Similar to our present results, Saad et al [21] and Imamura et al [17] showed a significant correlation between lymphatic invasion in the entire tumor tissue detected on D2-40 staining and depth of tumor invasion, stage, and lymph node metastases. Our analysis suggests that both itLVI and ptLVI promote malignant progression of esophageal cancer.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We THORACIC SURGERY also found that the presence of both itLVI and ptLVI significantly correlated with tumor size, tumor depth, TNM stage, and residual tumor. Similar to our present results, Saad et al [21] and Imamura et al [17] showed a significant correlation between lymphatic invasion in the entire tumor tissue detected on D2-40 staining and depth of tumor invasion, stage, and lymph node metastases. Our analysis suggests that both itLVI and ptLVI promote malignant progression of esophageal cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that intratumoral lymphatic vessels were found in large tumors and in tumors that had already spread to regional lymph nodes. Several reports have shown that increased ptLVD is positively associated with prognostic factors, including lymph node metastasis in patients with gastric, and esophageal cancer [20,21]. This suggests that both high itLVD and high ptLVD have important roles in maintaining an appropriate environment for tumor cells and could enhance the entrance of tumor cells into lymphatic vessels by increasing the contact surface between lymphatic vessels and tumor cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has previously been demonstrated that D2-40 was a lymphatic endothelial cell marker with high specificity, thus the present study used D2-40 to mark the lymphatic endothelial cells in ESCC and normal esophageal tissues, and to determine the LVD (17,18). The present study revealed that LVD was high in the tumor microenvironment surrounding ESCC, and were irregular in shape and exhibited the extended state.…”
Section: Discussionmentioning
confidence: 99%